Potrzeby informacyjne controllingu sprzedaży - Iwaniec, Magdalena Anna (The Information Needs of Sale Controlling, 2005)
The paper treats on the information needs, which are important element of sale controlling. Used information must possess qualitative characteristic. The information needs of sale controlling are satisfied by accounting and environment. Essential source is Customer Relationship Management. Information in sale controlling creates the basics for planning and controlling.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 208-211